Optimal fiscal policy with Epstein-Zin preferences and utility-enhancing government services: lessons from Bulgaria (1999-2016) - Aleksandar Vasilev (ZBW – Leibniz Information Centre for Economics, 2018)
This paper explores the effects of fiscal policy in an economy with Epstein-Zin (1989, 1991) preferences, with indirect (consumption) taxes, and all (labor and capital) in- come being taxed at the same rate. To this end, a dynamic general-equilibrium model, calibrated to Bulgarian data (1999-2016), is augmented with a government sector. Two regimes are compared and contrasted - the exogenous (observed) vs. optimal policy (Ramsey) case. The focus of the paper is on the relative importance of consumption vs. income taxation, as well as on the provision of utility-enhancing public services. The main findings from the computational experiments performed in the paper are: (i) The optimal steady-state income tax rate is zero; (ii) The benevolent Ramsey planner provides the optimal amount of the utility-enhancing public services, which are now 25% higher; (iii) The optimal steady-state consumption tax needed to finance the optimal level of government spending is more than fifty percent higher, as compared to the exogenous policy case.
Keywords: D58; 330; Epstein-Zin preferences; consumption tax; income tax; general equilibrium; optimal (Ramsey) fiscal policy; Bulgaria